2017
DOI: 10.1007/s10535-016-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the high-affinity phosphate transporter PHT1;4 gene promoter of Arabidopsis thaliana in transgenic wheat

Abstract: The root specificity and phosphate (Pi) deficiency responsiveness of high-affinity phosphate transporter (PHT1) genes point to their promoters as a sustainable system to drive Pi acquisition-related transgenes in plants. In this study, a 3-kb promoter of the AtPHT1;4 gene from Arabidopsis thaliana fused to the -glucuronidase (GUS) reporter gene was biolistically introduced into wheat (Triticum aestivum L.) and functionally characterized in transgenic plants grown in hydroponics and in pots with soil under var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This AtPHT1;4 promoter system can be used to improve the rhizosphere for maize and improve soil Pi uptake efficiency when maize plants experience Pi stress . A similar approach using the promoter of AtPHT1;4 in transgenic rice lines showed that high soil Pi content significantly inhibited the number of GUS transcripts …”
Section: Root Hair Development and Adaptation Under Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This AtPHT1;4 promoter system can be used to improve the rhizosphere for maize and improve soil Pi uptake efficiency when maize plants experience Pi stress . A similar approach using the promoter of AtPHT1;4 in transgenic rice lines showed that high soil Pi content significantly inhibited the number of GUS transcripts …”
Section: Root Hair Development and Adaptation Under Abiotic Stressmentioning
confidence: 99%
“…224 A similar approach using the promoter of AtPHT1;4 in transgenic rice lines showed that high soil Pi content significantly inhibited the number of GUS transcripts. 225 Magnesium (Mg) Deficiency. Magnesium is an essential mineral element for chlorophyll synthesis and therefore plays a critical role in the aboveground parts of plants.…”
Section: Under Abiotic Stressmentioning
confidence: 99%
“…For plant root system, the processes of phosphorus absorption from environment and transfer of the phosphorus nutrient to tissues and cells are mediated by a phosphate transporter (PT) located in the plasma membrane (23). There have been several reports on phosphate transporter genes in wheat (24)(25)(26), but most studies on this field have aimed only at function of these genes and regulation of phosphate transporters by arbuscular mycorrhizal fungi in wheat (24,26,(27)(28)(29), and few studies have focused on regulatory effects of PGPR on these genes in wheat. TaPT4, one member of high-affinity phosphate transporter gene, was found to have strong affinity to phosphorus, and to play a significant role in the absorption of phosphorus under conditions of low phosphorus stress in wheat (26,(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The P1BS element acts as the binding site for the PHR1 protein, a MYB transcription factor, presumably controlling the Pi starvation response in plants [55]. The substantial conservation of this candidate motif in other Pi transporter promoters in Arabidopsis, rice, barley, wheat, eggplant, and soy bean indicates that it is functionally conserved and may play a role in boosting root expression under Pi-deficient circumstances [53,[55][56][57][58][59][60]. Secondly, a number of root-specific regulatory elements, including ROOTMOTIFTAPOX1, OSE1ROOTNODULE, and OSE2ROOTNODULE, and other tissue-specific elements like CACTFTPPCA1, CAATBOX1, GTGANTG10, CCGTCC-box, and CAT-box were also discovered.…”
Section: Discussionmentioning
confidence: 99%